Squamata, Polychrotidae, Anolis chrysolepis Duméril and Bibron, 1837: distribution extension - Cybele Araujo (Check List, 2011)
The genus Anolis is the most diverse reptile genus with about 370 species widespread in Central and South America and the Caribbean. The distribution of Anolis chrysolepis Duméril and Bibron, 1837 extends from the northern portions of South America until southeastern Brazil. Herein, I provide two geographic coordinates that extend the known distribution of A. chrysolepis in southeastern Brazil.